Gilles Deleuze e o circuito vitalista das intensidades entre arte e filosofia - Fernando Tôrres Pacheco (2023)
A simple problem initially guides the paths this dissertation will take: is it possible to assert that there is an aesthetic in Gilles Deleuze's thought? Among the body of work produced by Deleuze, there is a vast amount of research revolving around the arts (literature, music, visual arts, cinema, etc.). The arts are present in books thematically relative to them exclusively, and are also implied in works that are apparently focused only on philosophy. Because Deleuzian thought itself is defined by a transversal alliance with other fields of knowledge, all of his writings are impregnated with themes not restricted to philosophy and the construction of concepts. However, acknowledging that Deleuze is never included among the most renowned philosophers in the area of Aesthetics, the initial question becomes pressing. We shall therefore see how the thought of Difference, while refusing the assumption of representationality, is compelled to establish zones of contact with the arts, as a way to expand its own field of meaning. Philosophical thought has no hierarchical primacy over artistic thought, and both domains collaborate in order to create new concepts and beings of sensation. In this sense, a genetic perspective is adopted, which animates these thoughts, and its primary instance is intensity. Deleuzian assumptions thus exposed, the intensive circuits established between art and philosophy incites us to investigate painting and its procedures - and what, in painting, elevates thought’s potency to create philosophical concepts. This investigation is only possible by summoning visual artists who develop thoughts about the act of painting. Among many others, artist Francis Bacon features prominently, considering Deleuze’s book Francis Bacon: the logic of sensation. After traversing these crossroads, we shall be able to answer the question which set in motion this dissertation.